Colonial Contacts and Individual Burials: Structure, Agency, and Identity in 19th Century Wisconsin - (:unkn) unknown (My University, 2014)
Individual burials are always representative of both individuals and collective actors. The physical remains, material culture, and represented practices in burials can be used in concert to study identities and social personas amongst individual and collective actors. These identities and social personas are the result of the interaction between agency and structure, where both individuals and groups act to change and reproduce social structures. The three burials upon which this study is based are currently held in the collections of the Milwaukee Public Museum. They are all indigenous burials created in Wisconsin in the 19th century. Biological sex, stature, age, and pathologies were identified from skeletal analysis and the material culture of each burial was analyzed using a Use/Origin model to attempt to understand how these individuals negotiated and constructed identities within a colonial system.
Keywords: Bioarchaeology; Fur Trade; Mortuary Archaeology; Native American; Structuration; Wisconsin